What lies beneath? Predictors of identification with all humanity. (15th April 2019) - Hamer, Katarzyna; McFarland, Sam; Penczek, Marta
Abstract: Superordinate identities, such as identification with all humanity (IWAH), may be considered the result of situational activation or as individual differences that can be measured using psychometric scales. Our research originates from this second approach. Why do some people feel connected only to narrow social groups like family and friends, while the social identifications of others cross boundaries, extending to people all over the world? We examined the possible psychological characteristics underlying this phenomenon in two cross-sectional studies ( N = 334, N = 311). A structural model of the effects of openness to experience, empathy (empathic concern and perspective taking), and universalism-tolerance, mediated by right-wing authoritarianism (RWA), social dominance orientation (SDO), and ethnocentrism upon IWAH is presented and tested. Results showed that openness to experience, empathy, and universalism-tolerance directly enhanced identification with all humanity. RWA, SDO and ethnocentrism were their partial negative mediators. SDO and ethnocentrism also directly reduced IWAH. These studies offer possible reasons for individual differences in levels of global human identification, by considering its psychological background. Highlights: The model of predictors of identification with all humanity (IWAH) was tested. Openness to experience, empathy, and universalism-tolerance directly enhanced IWAH. SDO and ethnocentrism directly reduced IWAH. RWA, SDO and ethnocentrism were also partial negative mediators in this model.